The Development of Advanced Materials - High Performance Properties of Composite for Automotive and Aerospace Applications - Idris, Jamaliah; Tan, J. C.; Chang, C. W. (Universiti Putra Malaysia Press, 2001)
Magnesium metal matrix composite (MMC) is an excellent candidate for moving engine components and airframes due to its low density. Magnesium's lightweight and natural affinity for wetting to ceramic particle reinforcements such as silicon carbide (SiC) make it one of the best choices as a matrix metal. However, magnesium alone without reinforcement is not suitable for mechanical applications due to its low wear resistance performance. The magnesium matrix composites used in this study were produced by powder metallurgy technique. The wear resistance of SiC/AZ91 composite reinforced with 0, 5, 10, 15 and 20 wt.% SiC were studied. Pin-<>n-disk dry sliding wear tests were carried out to study the volumetric wear, wear rate and wear mechanisms. The magnesium matrix composites were used as pins while the counter face consisted of mild steel disks. Worn surfaces of pins and the wear debris were investigated by using Scanning Electron Microscopy (SEM) and Energy Dispersive X-Ray Analysis (EDX). The wear resistance performance of magnesium matrix composites was found to improve with increasing volume fraction of SiC. Volumetric wear was found to increase with sliding distance and the wear rate was greatly reduced after the wear-in phenomenon. For AZ91 Mg-SiCp/ steel dry sliding wear system, 2D-wt.% SiC/AZ91 magnesium composite was found to have the best wear resistant performance. During the wear-in period, abrasion was predominant during the wear-in stage. In the corrosion study, corrosion behavior of Mgbased metal matrix composites SiC particulate reinforced AZ91 (SiC/AZ91) with reinforcement weight fraction of 5, 10, 15 and 20 wt.% as well as the monolithic AZ91 alloy was studied. The galvanic effect of SiC reinforcement on the matrix alloy was also investigated. The studies were carried out under temperature of 30° ± 1°C and pH 7 in aerated 0.1 M NaCI solution. The materials were studied by using electrochemical corrosion test, weight-loss measurement of corrosion rate, elemental analysis, X-ray diffraction and microscopic examination. The corrosion rates of the composites increased with the increase of SiC weight fraction. The significance of galvanic effect of SiC on the matrix alloy was proven where intersection of superimposed Tafel curves between sintered SiC and monolithic AZ91 occurred at higher corrosion current density (i...,) and lower corrosion potential (E...,). The corrosion was found localized at low SiC weight fraction, and gradually change to general corrosion. The corrosion rates of the composites were at least three times higher than the monolithic AZ91, due to galvanic effect of SiC on the matrix alloy and detachment of SiC particles from the materials.